Penerapan Metode Kooperatif Tipe Talking Stick Untuk Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran IPS Di Kelas VI SDN 45 Oto Ledang - Natalia Fansiska; Selfi Septiani; Muhammad Arif (JURNAL ARMADA PENDIDIKAN, 2024)
The initial problem that was the basis for conducting this research was that the learning method was less varied, namely lectures, as a result it did not attract students' interest and caused student activity to be low, student completion in social studies learning was still low, namely 8 students or around 28.57% of the total of 28 students. This means that most students do not complete. The aim of this research is to improve student learning outcomes by using the talking stick type cooperative learning method in class VI of SD Negeri 45 Oto Ledang. This research is a type of classroom action research. The subjects in this research were class VI students at SD Negeri 45 Oto Ledang with a total of 28 students. The results obtained by students in cycle 1 increased by 25% in cycle II. Initially the percentage of student completion was 57% and changed to 82% in cycle II. So it can be concluded that the use of the talking stick method is effective in improving student learning outcomes in social studies learning in class VI SD Negeri 45 Oto Ledang.